The importance of information quality in acquiring health information on social media during COVID-19: 106 the case of young adults in Klang Valley / Fatin Nurliyana Mior Yusoff and Azman Mat Isa - Mior Yusoff, Fatin Nurliyana; Mat Isa, Azman (Faculty of Information Management, 2022)
The emergence of COVID-19 has heightened global interest in health information. The public is increasingly reliant on social media platforms for acquiring and exchanging various sorts of information. With the growth of health information hoaxes, particularly during the epidemic, Malaysians who actively seek health information on social media would be at risk. The inability of certain people to critically evaluate the contents of COVID-19 resulted in their disseminating misleading information. With the rising interest in health information and social media, it is interesting to investigate the importance of health information acquisition on social media during COVID-19 among young adults.